Criteria to Qualify Microorganisms as “Probiotic” in Foods and Dietary Supplements - Binda, Sylvie; Hill, Colin; Johansen, Eric; Obis, David; Pot, Bruno; Sanders, Mary Ellen; Tremblay, Annie; Ouwehand, Arthur C. (Frontiers in Microbiology, 2020)
Still relevant after 19 years, the FAO/WHO definition of probiotics can be translated into four simple and pragmatic criteria allowing one to conclude if specific strains of microorganisms qualify as a probiotic for use in foods and dietary supplements. Probiotic strains must be (i) sufficiently characterized; (ii) safe for the intended use; (iii) supported by at least one positive human clinical trial conducted according to generally accepted scientific standards; and (iv) alive in the product at an efficacious dose throughout shelf life. We provide clarity and detail how each of these four criteria can be assessed. The wide adoption of these criteria is necessary to ensure the proper use of the word probiotic in scientific publications, on product labels, and in communications with regulators and the general public.